The mausoleum on the Red Square. Message in German, dated: 'Moskau, 1.Juni 1931', by ? to Fritz Brupbacher and his wife on back
The mausoleum on the Red Square. Message in German, dated: 'Moskau, 1.Juni 1931', by ? to Fritz Brupbacher and his wife on back.